Efektivitas Pendayagunaan Zakat Produktif Laz Harfa dalam Pemberdayaan Kelompok Usaha Mikro Berbasis Perempuan di Kota Serang pada Masa Endemi Covid-19 - Hadi Priatna, Umar; Said, Syihabudin; Atiah, Isti Nuzulul (Universitas Muhammadiyah Surabaya, 2024)
This research aims to analyze the effectiveness of LAZ Harfa's productive zakat utilization in empowering women-based micro bussines groups in Serang City. The object of this research is the members of the Urban KKM assisted by LAZ Harfa. The method used in this research is descriptive qualitative with the Miles and Huberman model data analysis method.The results of this study indicate that: 1) the utilization of LAZ Harfa's productive zakat in Serang City is carried out through the Urban Microfinance Group program which is given to housewives or widows who have businesses such as small traders, stalls, and food vendors who sell their merchandise at home and are included in the eight asnaf. In this KKM program, capital assistance is channeled to mustahik in the form of capital loans with several stages of loans using the qardul hasan contract 2) analysis of the effectiveness of the Urban KKM program based on all indicators obtained a percentage value of 90% which is included in the very effective category. The Urban KKM program is able to improve the economy of mustahik, its achievement can be seen from mustahik can develop their business, increase their income and free mustahik from usury debt. Keyword: Effectiveness, Empowerment, Productive Zakat Utilization